Determinant Financial Distress in Multi-Industrial Sector Companies - Kumba Digdowiseiso (LPMP Imperium, 2022)
Much research on predicting factors of financial distress has been carried out. However, few have objected in various industrial sectors, especially regarding debt-to-asset ratio, current ratio, and earnings per share. Therefore, this study aims to examine the effect of the determinants that predict financial distress in the various industrial sectors in 2016 - 2020, which are limited to the debt-to-asset ratio, current ratio, and earnings-per-share factors. The population of 35 companies is companies in the various industrial sectors listed on the Indonesia Stock Exchange from 2016 to 2020. The purposive sampling method was chosen as the sampling technique, and obtained 21 companies matched the criteria. Analysis of the data using a panel data logistic regression approach with a significance level of 0.05 using STATA 13 software. The data processing results with panel data logistic regression provide insight that only the current ratio or liquidity ratio predicts financial distress. In contrast, the other two factors, namely the debt-to-asset ratio, are significant. The representation of the size of the ratio of leverage and profitability with earnings per share is not able to predict financial distress. Suggestions for companies to pay attention to the liquidity ratio.